Case reports of covert use of phenobarbital in patients taking diankexing and diankening, traditional herbal medicine for epilepsy - Khean Jin, G.; Wee Tah, M.; Mustafa, A.M.; Chong Tin, T. (2004)
This is a report of three patients with drug resistant epilepsy, who was prescribed Diankexing and Diankening, herbal medicine for treatment of epilepsy by the traditional Chinese medicine physicians. Analysis of the medications from all the 3 patients showed Diankexing to contain phenobarbital, and Diankening from one patient. One patient had overt phenobarbital toxicity, and two others had phenobarbital side effects. Physicians should be aware of possible adulterations with conventional antiepileptic drugs in patients purported taking traditional medicine, with potential adverse effects and drug interactions.